The Concept of Family in Islamic Philosophy of Education: An Analysis of the Role of Mothers as First Educators - Tria Firda Aulia; Nasikhin; Fihriz (STIKes Ibnu Sina Ajibarang, 2025)
This article aims to analyze the concept of family in Islamic educational philosophy, with a special emphasis on the role of the mother as the primary educator. In the Islamic view, the family is considered the smallest and most fundamental social unit for a child, which has an important role in shaping their character and morality. As a central figure in the family, the mother plays a crucial role in instilling religious, ethical, and social values ​​from an early age. This study adopts a literature study approach to examine various philosophical and theological concepts related to education in the context of the Islamic family. Interactions in the family environment play a major role in instilling basic education for children, where the mother acts as their first madrasah. The findings of the study indicate that the role of the mother is not only limited to the aspect of physical maintenance, but also includes in-depth spiritual and intellectual education. Parents are expected to have adequate knowledge and education, so that children get adequate learning opportunities, and the education provided by parents can have a positive impact on the development of children's learning achievements. This article also raises the modern challenges faced by Muslim families in carrying out their educational functions, and offers practical solutions based on Islamic principles. This study provides theoretical contributions by enriching the study of Islamic educational philosophy through an emphasis on the strategic role of mothers in children's character education. Practically, this article presents solutions based on Islamic values ​​to face the challenges of education in today's Muslim families, so that it can be a reference for parents, educators, and policy makers in building a generation of Muslims with noble character. It is hoped that this article can provide a deeper understanding of the importance of the role of mothers in forming a generation of Muslims with noble character and contributing positively to society.